Aschizomys lemminus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
63. Lemming Mountain Vole Aschizomys lemminus French: Campagnol lemming / German: Lemming-Gebirgswiihimaus / Spanish: Topillo de montana lemming Other common names: Lemming Vole Taxonomy. Aschizomys lemminus G. S. Miller, 1899, “Kelsey Station, Plover Bay, Bering Strait, [Chukotskiy], Siberia [Russia].” In the past, A. lemminus was frequently classified as a species of Alticola or a subspecies of Myodes macrotis (as Alticola macrotis or Aschizomys macrotis). Monotypic. Distribution. E Siberia and Russian Far East (E of Lena River and Yablonoi Mts E to Chukchi Peninsula). Descriptive notes. Head-body 88- 120 mm,tail 10-28 mm; weight 21-39 g. Lemming Mountain Vole is small relative to species of Alticola. Tail is 16-24% of head-body length, is densely covered with hair, and has distinct tuft; it is distinctly bicolor, blackish brown above and gray below. Summer pelage is ash gray washed brown, belly is whitish gray, and demarcation on flanks is distinct. In most populations, winter pelage is whitish, washed ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 307-308, DOI: 10.5281/zenodo.6707142 ...